International Creative Product Exchange - Wyszkowska-Kuna, Joanna (Comparative Economic Research. Central and Eastern Europe, 2010)
The aim of this paper is to analyze and evaluate international trade in creative products with respect to the position of Poland in this exchange. In the introduction some definitions of creative industries and the concept of creative economy are presented. Then the classification of creative products in international trade and some problems with collecting data relating to international trade in creative products are discussed. In further work an empirical analysis of international trade in creative products is carried out. This work is divided into two parts. The aim of the first part is to indicate main tendencies and key players in international creative products exchange. The aim of the second part is to analyze the position of Poland in this exchange. The empirical analysis is based on the first database and report relating to international creative products exchange, published in 2008 by UNCTAD.